Factors Affecting the Mindset in Cultivating Management Major’s Students’ Entrepreneurship Spirit - Mutia Sari Dewi; Zuhrinal M. Nawawi (Indonesian Journal of Multidisciplinary Science, 2022)
The mindset of an entrepreneur is influenced by several factors such as environmental factors, association with the community, education, and experience. This study aims to determine what factors influence the entrepreneurial mindset to foster an entrepreneurial spirit in the Management Study Program students at the State Islamic University of North Sumatera. This research model uses a qualitative approach with survey and interview methods and involves 56 people. The results of this study indicate that the factors that influence the entrepreneurial mindset of Management Study Program students at the State Islamic University of North Sumatera are environmental factors, association with the community, education, and experience. The way to develop an entrepreneurial mindset in the Management Study Program students at the State Islamic University of North Sumatra is by developing a positive mindset and avoiding negative thinking patterns.